Sector heterogeneity and wage inequality. Issue 6 (2nd November 2021) - Pi, Jiancai; Fan, Yanwei
ABSTRACT: This paper takes heterogeneity between different skilled sectors into account and analyzes how sector heterogeneity affects wage inequality through the general equilibrium approach. We find that under both the wage efficiency hypothesis and the fair wage hypothesis, an increase in the degree of sector heterogeneity will conditionally expand wage inequality between skilled workers in the high-productivity skilled sector and the low-productivity skilled sector and that between skilled and unskilled labor.